The extraction and process optimization of Cu (II) and Cd (II) using Pickering emulsion liquid membrane - P. Murugan (IWA Publishing, 2021)
In the present study, the extraction of divalent heavy metals like copper [Cu (II)] and cadmium [Cd (II)] using a Pickering Emulsion Liquid Membrane (PELM) has been investigated by using three different surfactants such as Amphiphilic silica nanowires (ASNWs), Aluminum oxide nanoparticles (Alumina) and Sorbitan monooleate (SPAN 80). The influence of the process parameters such as pH, the stripping phase concentration, the agitation speed, and the carrier concentration on the extraction efficiency have been examined to find the optimum conditions at which the maximum recovery of Cu (II) and Cd (II) could take place. At optimum conditions, the extraction efficiency of 89.77% and 91.19% for Cu (II) and Cd (II) ions were achieved. Non-edible oils were used as diluent in this present study to reduce the need for toxic organic solvents in preparing PELM. The impact of each process factor on the extraction efficiency of Cu (II) and Cd (II) ions has been verified using analysis of variance (ANOVA). The higher values of F and lower values of P (less than 0.05) indicate pH is the most significant parameter on the percentage extraction of Cu (II) and Cd (II) using the Taguchi design approach. HIGHLIGHTS Removal of Cu (II) and Cd (II) using PELM.; Extraction performance has been compared for the three different surfactants such as ASNWs, Alumina and SPAN 80.; Non-edible oil such as Pungai oil was used as diluent.; Effect of various parameters on Cu (II) and Cd (II) removal were studied and optimized using the Taguchi approach.; Probable interactions between each parameter and efficiency have been studied.;